Influence of dietary patterns on anxiety (Research, Society and Development, 2022)
Introduction: Anxiety is an increasingly prevalent mental disorder that affects the quality of life of individuals worldwide. Although medication is one of the main interventions, current studies seek to understand the contribution of food to the mental health of these individuals. Objective: The objective of this study was to understand, through an integrative literature review, the impact of dietary patterns on anxiety disorder. Methodology: The search sources were the databases: National Library of Medicine (PubMed) and MDPI (Nutrients), with the selection of articles published in national and international journals, from 2014 to 2021. The choice of this period met the criterion of temporality, in which the time frame of ten years was considered, as these are more current publications, in English and Portuguese. Results and discussion: In the analyzed studies, it was found that depending on the nutritional quality of the diet, it can contribute as a therapeutic resource to improve anxiety symptoms or exacerbate the symptoms of this disorder. The importance of healthy eating patterns impacting the improvement of anxiety symptoms was highlighted, such as the Mediterranean diet and specific micronutrients such as tryptophan and omega 3. Final considerations: Thus, it is concluded that nutritional intervention is recommended because the evidence indicates a direct relationship between diet and mental health.